Resistência cruzada aos fungicidas IQo azoxistrobina e piraclostrobina no patógeno da brusone do trigo Pyricularia oryzae no Brasil - de Oliveira, Samanta Cristiene [UNESP]; Castroagudín, Vanina Lilián [UNESP]; Maciel, João Leodato Nunes; Pereira, Danilo Augusto dos Santos [UNESP]; Ceresini, Paulo Cezar [UNESP] (FapUNIFESP (SciELO), 2015)
Strobilurins are among the fungicides that are most commonly used in the control of wheat diseases, separately or in mixtures with fungicides that inhibit the enzyme succinate dehydrogenase (SDH). Strobilurins are known as quinone oxidoreductase inhibitors or QoI fungicides. As in fungal cells they have one single site of action as target, the mitochondrial cyt b gene, the continued use of strobilurins may represent a high risk of emergence of resistance to these fungicides for plant pathogens populations. This study aimed to test the hypothesis that resistance to azoxystrobin in the wheat blast fungus Pyricularia oryzae resulted in cross-resistance to pyraclostrobin, another QoI fungicide. To test this hypothesis, we compared the level of pyraclostrobin resistance presented by two groups of P. oryzae isolates from wheat: a) sensitive to azoxystrobin and carrier of the non-mutant cyt b gene (haplotype H9), and b) resistant to azoxystrobin and carrier of the G143A mutation in the cyt b gene (H1 haplotype). Fungicides belonging to the same chemical group show cross-resistance. All P. oryzae isolates sensitive to azoxystrobin were also sensitive to pyraclostrobin. Isolates that were resistant to azoxystrobin were also resistant to pyraclostrobin, indicating cross-resistance to both fungicides. Two phenotypic groups were distinguished among the resistant isolates: (A) highly resistant and (B) resistant. P. oryzae isolates with the presence of G143A mutation in the cyt b gene were 42 times more resistant to pyraclostrobin. These high levels of resistance to QoI fungicides may be the result of high selection pressure exerted by consecutive years of strobilurin application for the management of wheat diseases in Brazil.
Cross-resistance to QoI fungicides azoxystrobin and pyraclostrobin in the wheat blast pathogen pyricularia oryzae in Brazil
Keywords: Cytochrome b; EC50; Quinone oxidoreductase inhibitors; Strobilurin; Triticum aestivum